2011
DOI: 10.1063/1.3637047
|View full text |Cite
|
Sign up to set email alerts
|

Surface loss simulations of superconducting coplanar waveguide resonators

Abstract: Losses in superconducting planar resonators are presently assumed to predominantly arise from surfaceoxide dissipation, due to experimental losses varying with choice of materials. We model and simulate the magnitude of the loss from interface surfaces in the resonator, and investigate the dependence on power, resonator geometry, and dimensions. Surprisingly, the dominant surface loss is found to arise from the metalsubstrate and substrate-air interfaces. This result will be useful in guiding device optimizati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
190
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(213 citation statements)
references
References 19 publications
17
190
1
Order By: Relevance
“…64 The substrate/superconductor interface is also critical to device performance. 88 Vissers et al demonstrated this for TiN growth. 62 They found that careful cleaning of the Si wafer, followed by a brief nitridation of the Si surface just prior to TiN deposition, yielded CPW resonators with Q ∼ 10 6 at low powers (see Figure 6b ).…”
Section: What Resonators Can Tell Us About Materials and Fabricationmentioning
confidence: 89%
See 1 more Smart Citation
“…64 The substrate/superconductor interface is also critical to device performance. 88 Vissers et al demonstrated this for TiN growth. 62 They found that careful cleaning of the Si wafer, followed by a brief nitridation of the Si surface just prior to TiN deposition, yielded CPW resonators with Q ∼ 10 6 at low powers (see Figure 6b ).…”
Section: What Resonators Can Tell Us About Materials and Fabricationmentioning
confidence: 89%
“…58 However, resonator electric-fi eld simulations indicatd that the metal-substrate and substrate-air interfaces could dominate the surface loss. 88 With these results in mind, more recent work on resonator (and qubit) materials has centered on ways to either prepare the substrate better or use materials that are less susceptible to contamination in device processing or oxidation in air.…”
Section: What Resonators Can Tell Us About Materials and Fabricationmentioning
confidence: 99%
“…These are relatively large numbers, an indication of large variations of electric field distribution across the resonant structure and interaction with many differently coupled TLFs. 7,26 The relatively low saturation quality factor also indicates that a large number of TLFs are involved, as expected from the fractal geometry. However, the magnetic field induced loss rates will still be dominating in this structure at the magnetic fields required for free spin interaction.…”
Section: Power Dependencementioning
confidence: 94%
“…The remaining dissipation channel is usually attributed to the presence of TLFs. The exact nature of TLFs remains contentious, but a variety of experiments have studied their effects [8][9][10][11][12] and recent models evaluated the contributions of TLFs in varying locations [13].In this letter we study slow noise processes in low loss niobium (Nb) on sapphire resonators [11]. Resonators are by their very nature sensitive probes: any change in the environment will produce a change in the centre frequency ν 0 of the resonator; making them ideal devices for studying noise.…”
mentioning
confidence: 99%
“…The remaining dissipation channel is usually attributed to the presence of TLFs. The exact nature of TLFs remains contentious, but a variety of experiments have studied their effects [8][9][10][11][12] and recent models evaluated the contributions of TLFs in varying locations [13].…”
mentioning
confidence: 99%